The Effectiveness of a linear Algebra Teaching Program based on the Graph Theory in Developing the Geometric Sense Skills among Mathematic Students at Faculty of Education Sana'a - Alsabri, Afrah AbdAlrkeep; Saeed, Radman Mohamed (Journal of Curriculum and Teaching Methodology, 2023)
The study aims to know the effectiveness of a teaching program in linear algebra based on the graph theory in developing the geometric sense skills among Mathematic students at faculty of Education. In this study, the quasi-experimental approach with design of one group (pre-test and post-test). The sample of the study was 34 students of the second level, Department of Mathematics, Faculty of Education, Sana'a University, for collecting data, a scale of geometric sense skills was built, The results of this study showed that there were statistically significant differences at the level of significance (0.05) in students' acquisition of geometric sense skills in favor of the post-test.In the light of results of study, it is recommended to pay more attention to building educational programs based on the theory of the graph in improving mathematical skills and the thinking of the students.
Keywords: graph theory; linear algebra; geometric sense